TOT Literasi Informasi (Materi TOT LI untuk Pustakawan UM Purwokerto) - Novy Diana Fauzie (perpustakaan UMY, 2016)
"To be information literate, a person must be able to recognize when information is needed and have the ability to locate, evaluate, and use effectively the needed information". (Presidential Committee on Information Literacy. 1989, p. 1).